Design of high PSRR voltage reference using current-mode approach - Lian, Tong Wei. (2011)
A Bandgap Voltage Reference (BVR) is a circuit whose output is independent to variations temperature, process, supply voltage and noise. It is required in many integrated circuits to ensure their proper functionality. A current mode approach OTA based Bandgap Voltage Reference design is proposed in this project.